The reasons for delaying the age of marriage among Algerian youth - a field study in some municipalities of the state of Jijel – - Bouamoucha, Naim (Social Empowerment Journal, 2021)
Despite the great importance of marriage in ensuring psychological and social stability and the survival of the human kind, the spread of the phenomenon of delaying the age of marriage among young people in Algerian society has exceeded the established limits in recent years, due to the changes that affected the social, cultural, intellectual and economic structures of society, and became threatening our society from within. With the increase in the number of singles among men, and the increase in the rate of spinsterhood among women. This study aimed to identify the reasons for delaying the age of marriage among Algerian youth, through a study of a sample of young people in some municipalities of the state of Jijel. The researcher used the descriptive method, and the questionnaire tool, to collect data from the respondents, whose number was estimated at 190 young men who were intentionally chosen. The study found that the reasons for delaying marriage among Algerian youth are: personal reasons in the first place, psychological reasons in the second degree, economic reasons in third place, and finally social reasons in fourth place.